Analisis Perlindungan Hukum Terhadap Debitor Dengan Jaminan Fidusia Atas Kendaraan Bermotor Di Indonesia - Abdul Muin; Iwan Hermawan; Tamin Tisna; Firman Nurdiyansyah Sunandar (Journal of Innovative and Creativity, 2025)
Financial institutions, both banks and non-banks, play a strategic role in business transactions in today's modern era. Almost no business activity today requires the services of financial institutions and banks, as the current transaction system is slowly shifting from manual transactions to digital transaction systems using electronic devices and internet connections. This reality is triggered by several reasons, including the fact that digital transaction systems are seen as providing greater convenience, speed, and practicality because they can be done anytime and anywhere without being limited by space and time. In providing credit, there is certainly an agreement and also a guarantee. One well-known guarantee institution is "Fiducia". The government has implemented credit policies through financial institutions, both government-owned and private, which can provide credit with low interest rates and easy requirements and other things. Fiducia itself is an old term that is already known in Indonesian. According to Law Number 42 of 1999 concerning Fiducia Guarantees, this is also called the term "transfer of ownership rights in trust." This study aims to analyze the settlement of debtor defaults in financing agreements with fiduciary collateral for four-wheeled vehicles based on the provisions of Law Number 42 of 1999 concerning Fiduciary Guarantees. This study uses a normative juridical method with a statutory and conceptual approach. The results indicate that default settlement can be carried out through the execution of the fiduciary collateral object based on a Fiduciary Guarantee Certificate, which has executorial power as stipulated in Article 29 of the Fiduciary Guarantee Law.